Chromatographic identification of leaf color characteristics on fine-flavor and bulk cacao as selection indicator - Indah Anita Sari; Bayu Setyawan; Marcelinus A.S. Adhiwibawa; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2016)
A problem encountered in plant breeding process to determine bean color quality of fine-flavor cocoa is a long selection period. Preliminary results indicatedthat the fine-flavor cocoa has a low color reflectance than bulk cocoa. The objectiveof this study is to find more applicable and easier method to do the early detectionof fine-flavor cocoa on the breeding population. Detection of the leaf color haracteristics was done by chromatographic and spectrophotometry analysis. hromatographic analysis was carried out in Kaliwining Experimental Station, IndonesianCoffee and Cocoa Research Institute using complete random design consistedof two types of cocoa; fine-flavor (10 clones) and bulk cocoa (10 clones). pectrophotometric analysis was conducted at Ma Chung University, Malang, East Java.Four clones of bulk cocoa and six clones of fine flavor cocoa were used in thisanalysis. The results of the study showed that the flush color characteristics of thefine-flavor cocoa were different from the bulk cocoa characteristics as shown bythe differences in the value of L*, b* and anthocyanin content. Flush characteristic s ofthe fine-flavor cocoa had brighter color, more toward green with higher yellowlevel, while the bulk cocoa had darker flush, red and lower yellow level. Thecolor parameter of L* and b* had a higher genetic variation compared with theenvironment variation. However, the parameter a* had a higher environmental variation compared with genetic variation. Grouping of fine-flavor cocoa and bulk cocoacould be done through the detection of flush anthocyanin content, when tendencyof flush anthocyanin content on fine-flavor cocoa was lower than bulk cocoa.The detection of flush color particularly L* and b* parameters through hromatographic analysis and anthocyanin content through spectrophotometric analysismay be used as a criteria for selection the fine flavor cocoa on seedling phase.